Squamous cell carcinoma of the renal pelvis presenting with a loin sinus - Giannopoulos, A; Mitropoulos, D.; Davaris, P.; Alivizatos, G.; Dimopoulos, M.A. (European Urology, 1989)
An unusual presentation of a renal pelvis squamous cell carcinoma is reported; a loin sinus with excessive pyorrhea was the only complaint of a man with a long history of renal calculus disease.
Keywords: kidney neoplasms; Lithiasis; Loin sinus; Squamous cell carcinoma